Reportando propriedades da madeira ao teor de umidade de referência - Soares, Rainy da Conceição (2014)
For a long time it is known that the wood strength varies with its moisture content. Increasing wood moisture content occurs a decrease in its mechanical strength, this variation in resistance is more sensitive to low levels of moisture content, and is practically negligible to high levels of moisture content. Happens from this fact, that to compare two species strength, or wooden pieces, to a specific request, it is necessary to establish a reference moisture content, because a lower strength species, with low moisture content, can to present higher strength that a greatest strength species, but with higher moisture content. The current Brazilian Code for the timber structures design adopts for reference, the 12% moisture content, to which all tests results must be reported. The hypothesis of this work is that when reporting results of tests made in wood green, to the 12% moisture content, the errors can be superior to 10%, therefore, unacceptable to timber structures design. The proper procedure would be to make an initial drying, on standard weather, until mass stabilization, that is, until it reaches the moisture content equilibrium with the environment, before making the tests. The objective of this work was to show that the results of tests conducted with very wet wood, i.e. with moisture content above the fibers saturation limit, cannot be adequately corrected for the 12% reference moisture content, because the error committed in this correction can overcome 10%. To this, results of tests conducted in air-dried wood and conditioned (values already close to 12% moisture content) were compared with those obtained in very wet wood, in this case wood saturated in water. These results were previously reported at reference moisture content. For statistical consistency were used 10 different species of wood. Of each species were conducted tests of compression parallel to the fibers (strength and stiffness), shear strength and specific gravity, on the three defined conditions for moisture. Using as variable the “relative error”, on the basis of the corrected value by expressions, already validated in the literature for the moisture interval between 10 and 20%, from the situation “conditioned wood”, Tukey test was applied and the results indicate that the corrections made from the situations "conditioned wood" and " air-dried wood" are statistically equivalents, but differ from corrections made from the situation "saturated wood". It is concluded, therefore, that to report tests results to the moisture content reference, these results can’t be obtained from tests on high moisture content wood. The specimens must be conditioned or air-dried before.